Conceitualismo: moderno, insuportável - Cury, David Abdala (1992)
Critical limits of Conceptualism in art ( whose historic cycle approximately dates from 1965 to 1975) and its practices (Art Language, Povera, Land Art and Body Art) of dematerialization of the art object (Modernism paradigm of the 20th century first half) are here thought as a verification of a possible rupture or continuity solution between what contemporary art and modern art supposedly are.